Optimalisasi Value Proposition Produk Juiceyo Di Kota Makassar - Adinda Putri; St. Sabahannur; Andi Azrarul Amri (Universitas Hamzanwadi, 2026)
Growing public awareness of healthy lifestyles is driving demand for natural, nutrient-rich fruit-based beverages. However, many juice products on the market still contain added sugar and water, which reduce their nutritional value. This study aims to analyze JuiceYo’s value proposition and its role in the development of the healthy beverage industry in Makassar. The methodology employed is qualitative descriptive analysis through the implementation of a business plan, market validation, and analysis of the Business Model Canvas (BMC) and Value Proposition Canvas (VPC). Data was collected through business observations, production trials, and consumer feedback surveys. The results indicate that JuiceYo’s primary advantage lies in its 100% pure juice products, free from added sugar, water, or preservatives, processed using the cold-pressed method to preserve nutritional content. Market validation revealed that the majority of consumers are dissatisfied with juices that are too sweet and watery, making this product well-suited to their needs. The target market includes urban residents, particularly Generation Z and millennials aged 20–34. With a price of Rp23,000 per bottle and a sales target of 196 bottles per month, JuiceYo has strong market potential. Optimizing the value proposition has proven crucial for enhancing competitiveness and business sustainability.